Pan-cancer analysis reveals PRRT4 is a potential prognostic factor of AML - Wenqiong Xiang; Fangjun Chen; Hao Zhou; Guilin Ren; Guangliang Qiang; Li Wang (Hematology)
Background: Proline-rich transmembrane protein 4 (PRRT4) has been infrequently studied, with limited literature suggesting its potential as a prognostic marker for gastric cancer. This study aims to investigate the prognostic value of the PRRT4 gene in pan-cancer.Methods: We acquired and analyzed data from several platforms, including The Cancer Genome Atlas (TCGA), Genotype Tissue Expression Project (GTEx), Cancer Cell Line Encyclopedia (CCLE), cBioPortal, HPA, and TIMER 2.0. In addition, we have further analyzed the data using multivariate analyzes and RT-qPCR. In vitro experiments were performed to detect the proliferation and apoptosis of AML cells before and after PRRT4 knockdown.Results: PRRT4 exhibited low expression in 10 types of cancers and high expression in 3 types, and this expression was significantly correlated with tumor stage, age, and gender across various cancer types. PRRT4, identified as a potential independent prognostic factor for overall survival (OS) in several cancers including LAML, PAAD, SKCM, STAD, THYM, and UVM, and exhibited a high frequency of mutation in UCEC. Moreover, PRRT4 was found to be correlated with DNA methylation and immune infiltration in various cancers. Ultimately, in the multivariate analysis model, PRRT4 was discerned as an independent prognostic biomarker for AML, predicated on the statistics based from our institution. After PRRT4 knockdown, the proliferation ability of THP1 cells was significantly enhanced, and the apoptosis ratio was significantly decreased.Conclusion: PRRT4 may serve as a potential therapeutic target and prognostic marker for various malignancies.